Arctic beans containers composition of non-functional services using composition filters - Blair, Gordon S.; Yang, Jie; Andersen, Anders (Universitetet i Tromsø, 2005)
It is becoming clear that modern middleware platforms must provide both deploy-time configuration and run-time reconfiguration to accommodate rapid changing requirements and also to be able to operate in dynamic environments. J2EE is a key example of a middleware architecture that supports enterprise applications via its Enterprise JavaBeans (EJB) component model. EJB provides limited configurability in terms of a fixed set of non-functional middleware services at deployment-time (via a declarative deployment descriptor). However, EJB along with other related enterprise architectures generally do not provide enough support for re-configuration or evolution. At best, there is limited support in some platforms for replacing or updating particular services. This paper discusses the design of configurable and re-configurable middleware architecture and also the key role of separation of concerns for such platforms. The paper also describes the Arctic Beans component model which uses the Composition Filters model to capture such concerns and also support their safe composition.The paper also explains how this model can be used to construct an Arctic Beans container, in the style of EJB. The main contribution of the paper is to demonstrate that adaptable middleware platform can be developed using separation of concern technologies, specifically the composition filters model.